7 4 − 7 2 5 + 7 3 4 − 7 4 5 + 7 5 4 − 7 6 5 + . . . . . . . . . . . . . ∞ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please don't use \ ( \ ) before every line.
Instead, get them all in one \ ( .... \ ) formatting, and use " \ \ " to make it appear on further line.
For example,
" 1+1 \ \ 2+2 \ \ 3+3 " (without spaces) will give you the output
1 + 1 2 + 2 3 + 3
Adding a \displaystyle code at starting of the \ ( \ ) formatting will make them appear better.
Log in to reply
Ok. Thanks!
Log in to reply
I've edited LaTeX of your solution for this problem and also the 1st part. Note that using \dfrac in place of \frac makes it clearer to view. So edit that in your solution now...
S = 7 4 − 7 2 5 + 7 3 4 − 7 4 5 + 7 5 4 − 7 2 5 6 + . . .
= 7 2 2 8 − 5 + 7 4 2 8 − 5 + 7 6 2 8 − 5 + . . .
= 4 9 2 3 ( 1 + 7 2 1 + 7 4 1 + 7 6 1 + . . . )
= 4 9 2 3 ( 1 − 4 9 1 1 ) = 4 9 2 3 ( 4 9 4 8 1 ) = 4 9 2 3 ( 4 8 4 9 ) = 4 8 2 3
Let S = 7 4 − 7 2 5 + ⋯ , then S = 7 4 − 7 2 5 + 7 2 S therefore making S the subject we get S = 4 8 2 3
Love your solution ! 😁
Let,s separate the question into 2 parts: 7 4 + 7 3 4 + 7 5 4 + ⋯ ) − ( 7 2 5 + 7 4 5 + 7 6 5 + ⋯ ) Now let,s find sum of each part separately. L e t S = 7 4 + 7 3 4 + 7 5 4 + ⋯ T h e n 7 2 S = 7 3 4 + 7 5 4 + ⋯ Subtracting the first equation from the second equation gives us: S − 7 2 S = ( 7 4 + 7 3 4 + ⋯ ) − ( 7 3 4 + 7 5 4 + ⋯ ) 7 2 4 8 S = 7 4 4 8 S = 7 4 × 7 2 = 4 × 7 = 2 8 → S = 4 8 2 8 = 1 2 7 Now let,s deal with the second part: L e t M = 7 2 5 + 7 4 5 + ⋯ T h e n 7 2 M = 7 4 5 + 7 6 5 + ⋯ Subtracting the first equation from the second equation gives us: M − 7 2 M = ( 7 2 5 + 7 4 5 + ⋯ ) − ( 7 4 5 + ⋯ ) 7 2 4 8 M = 7 2 5 → 4 8 m = 5 → M = 4 8 5 Now we have the necessary data.Subtracting the second fraction from the first gives the answer: 4 8 2 8 − 4 8 5 = 4 8 2 8 − 5 = 4 8 2 3 I know my solution is too long but this is the way I solved it becuse I wasnt introduced to the formula for sum of geometric series.
Problem Loading...
Note Loading...
Set Loading...
7 4 − 7 2 5 + 7 3 4 − 7 4 5 + 7 5 4 − 7 6 5 + . . . . . . . . . . . ∞
= ( 7 4 + 7 3 4 + 7 5 4 + . . . . . ∞ ) − ( 7 2 5 + 7 4 5 + 7 6 5 + . . . . . ∞ ) = 1 − 7 2 1 7 4 − 1 − 7 2 1 7 2 5 = 1 2 7 − 4 8 5 = 4 8 2 3